Proceedings of the 2011 ACM Symposium on Applied Computing 2011
DOI: 10.1145/1982185.1982402
|View full text |Cite
|
Sign up to set email alerts
|

Incremental multi-target model trees for data streams

Abstract: As in batch learning, one may identify a class of streaming real-world problems which require the modeling of several targets simultaneously. Due to the dependencies among the targets, simultaneous modeling can be more successful and informative than creating independent models for each target. As a result one may obtain a smaller model able to simultaneously explain the relations between the input attributes and the targets. This problem has not been addressed previously in the streaming setting. We propose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…Ikonomovska et al proposed an incremental multi‐target model tree algorithm, referred to as FIMT‐MT, for simultaneous modeling of multiple continuous targets from time changing data streams. FIMT‐MT extends an incremental single‐target model tree by adopting the principles of the predictive clustering methodology in the split selection criterion.…”
Section: Multi‐output Regressionmentioning
confidence: 99%
“…Ikonomovska et al proposed an incremental multi‐target model tree algorithm, referred to as FIMT‐MT, for simultaneous modeling of multiple continuous targets from time changing data streams. FIMT‐MT extends an incremental single‐target model tree by adopting the principles of the predictive clustering methodology in the split selection criterion.…”
Section: Multi‐output Regressionmentioning
confidence: 99%
“…In a regression context, an arguably similar setting to multi-label learning is the multitarget problem, that is addressed in Appice and Džeroski (2007), and on data streams in Ikonomovska et al (2011). However, we are not aware of any existing work dealing with this approach on multi-label data streams; the work done in this paper does not deal with any multi-label data sources, and thus is it not of specific relevance to this paper.…”
Section: Related Workmentioning
confidence: 99%
“…To utilize the MLC via MTR approach, we have reimplemented the FIMT and FIMT-MT algorithms (Ikonomovska et al 2011a) in the MOA framework to facilitate usability and visibility, as the original implementation was a standalone extension of the C-based VFML library (Hulten and Domingos 2003) and was not available as part of a larger data stream mining framework. We have also significantly extended the algorithm to consider nominal attributes in the input space when considering splitting decisions.…”
Section: The Isoup-tree Methodsmentioning
confidence: 99%
“…Ikonomovska et al (2011b) introduced an instance-incremental streaming tree-based singletarget regressor (FIMT-DD) that utilized the Hoeffding bound. This work was later extended to the multi-target regression setting (Ikonomovska et al 2011a) (FIMT-MT). There has been a theoretical debate on whether the use of the Hoeffding bound is appropriate (Rutkowski et al 2013), but, a recent study by Ikonomovska et al (2015) has shown that, in practice, the use of the Hoeffding bound produces good results.…”
Section: Multi-target Regressionmentioning
confidence: 99%